KVARKER, LEPTONER OG DEN OVERFLØDIGE SAMLING: Jagten på en teori for alting – og ingenting - Paaske, Jens (Tidsskriftet Antropologi, 2018)
The article views collections as non-random accumulations, i.e. objects with interrelations and a well hidden, unifying theme. In the greatest of all collections, referred to loosely as the universe, such interrelations make up the “laws of nature” of which we have already unravelled so many. The theme under which it was all put together, however, has still to be revealed. After briefly outlining the evolution in physics from Democritos’ atomic theory to the 19th century advent of the periodic table of the elements, the article continues with a descent into the finer details of matter, ending up at the quarks and leptons which constitute the matter particles of the so-called standard model of elementary particles. The collection of all matter hitherto observed in the universe has repeatedly been subjected to a reduction based on the rationale that seemingly different objects are identified merely as different manifestations of the same object. A simpler, yet representative collection is established once the emerging structures of the collection at hand have been properly resolved. It is the nature of this sobering reductionist process which is the topic in which the discussion draws upon a selection of examples from the ancient, as well as the more contemporary, history of physics.